HUBUNGAN BEBAN PENGASUH DAN TINGKAT STRESS DENGAN KUALITAS HIDUP FAMILY CAREGIVER PADA LANSIA YANG MEMILIKI PENYAKIT KRONIS DI KELURAHAN CIJORO LEBAK, BANTEN - Siska Aulia, (2023)
Chronic illness makes the elderly more dependent on family caregivers. If you are unable to adapt to the demands, it will cause burden and stress and impact on the quality of life of the family caregiver. The purpose of this study was to determine the relationship between caregiver burden and stress levels with the quality of life of family caregivers in the elderly who have chronic diseases in Cijoro Lebak Village, Banten. This study used a cross sectional approach using the Chi Square test. The sample collection technique used was total sampling on 98 respondents. The questionnaire used for caregiver burden (zarit burden interview), stress level (perceived stress scale) and quality of life (world health organization-BREF). These results indicate that there is a relationship between caregiver burden and stress levels with the family caregiver's quality of life with p values of 0.007 and 0.000. It is hoped that health service providers will facilitate family caregivers by holding training on caring for elderly people with chronic diseases, stress management and counseling related to the burden of caring. The findings of this study clarify previous research and provide additional information so that future researchers can dig deeper into other factors of quality of life. Keyword: Caregiver Burden, Elderly, Family Caregiver, Quality of Life, Stress Level